Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T18:06:46+01:00
A) -3x = 2x - 10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b) 2x - 2 = 7 - x
2x+x=7+2
3x=9/:3
x=3
c) 10 = 4 - 2x
10-4=-2x
6=-2x/:(-2)
-3=x
d) - (2x - 1) = 4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-1,5
e) 2 (x + 1) = x
2x+2=x/-2x
2=-x/^(-1)
x=-2
f) 2t - (3t + 1) = 6
2t-3t-3=6
-t=6+3
-t=9/^(-1)
t=-9
g) - (4 + x) = 2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h) 3(y + 6) - y = 2(y + 9)
3y+18-y=2y+18
2y+18=2y+18
y może być każdą liczbą!!!
i) (x - 7) - 2(3x + 5) = 3
x-7-6x-10=3
-5x-17=3/+17
-5x=20/:(-5)
x=-4
2010-02-22T18:07:11+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10/: (15)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/: 3
x = 3

c)10 = 4 - 2x
2x=4-10
2x=-6/: 2
x=-3

d) - (2x - 1) = 4
-2x+1=4
-2x=4-1
-2x=3/: (-2)
x=-1½

e) 2 (x + 1) = x
2x+2=x
2x-x=-2
x=-2

f) 2t - (3t + 1) = 6
2t-3t-1=6
2t-3t=6+1
-1t=7/: (-1)
t=-7

g) - (4 + x) = 2(3-x)
-4-x=6-2x
-x+2x=4+6
x=10

h) 3(y + 6) - y = 2(y + 9)
3y+18-y=2y+18
3y-y-2y=18-18
y=0

i) (x - 7) - 2(3x + 5) = 3
x-7-6x-10=3
x-6x=7+10+3
-5x=20/:(-5)
x= -4
2010-02-22T18:08:30+01:00
A) -3x = 2x - 10
-3x - 2x = -10
-5x = -10 : -5
x = 2
b) 2x-2 = 7 - x
3x = 9 : 3
x = 3
c) 10 = 4 - 2x
2x = -6 :2
x = -3
d) - (2x - 1) = 4
- 2x + 1 = 4
- 2x = 3 : (-2)
x = -1,5
e) 2 (x+1) = x
x = -1
f) 2t - (3t + 1) = 6
2t - 3t - 1 = 6
-1t = 7 : (-1)
t = -7
g) - (4 + x) = 2 (3 - x)
- 4 - x = 6 - 2x
x = 10
h) 3 (y + 6) - y = 2(y + 9)
3y + 18 - y = 2y + 18
0 = 0 równanie tożsamościowe
i) (x - 7) - 2(3x + 5) = 3
x - 7 - 6x - 10 = 3
-5x = 20 : (-5)
x = - 4